Hybrid Graphene–Giant Nanocrystal Quantum Dot Assemblies with Highly Efficient Biexciton Emission. Issue 1 (22nd September 2014) - Gao, Yongqian; Roslyak, Oleksiy; Dervishi, Enkeleda; Karan, Niladri S.; Ghosh, Yagnaseni; Sheehan, Chris J.; Wang, Feng; Gupta, Gautam; Mohite, Aditya; Dattelbaum, Andrew M.; Doorn, Stephen K.; Hollingsworth, Jennifer A.; et al.
<x xml:space="preserve">Abstract</x> A monolayer of graphene strongly enhances the bi‐exciton emission efficiency of CdSe/CdS core/thick‐shell nanocrystal quantum dots (NQDs), the so‐called "giant"‐NQDs. As an explanation, a new plasmon mode is proposed, resulting from local oscillations of excess hole density (the hole puddle) that is accumulated directly underneath a charged g‐NQD. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>